Mitigating Crime and Violence in Coca-growing Areas - Thomas Mortensen (Journal of Illicit Economies and Development, 2019)
Puzzled about why and how coca-growing areas in Bolivia do not have the same levels of violence and criminality experienced in their communities, eight peasant leaders from various coca-growing areas of Colombia joined a study tour to investigate. Notwithstanding differences in histories of conflict, political economy, infrastructure, and state-society relations, two explanations stood out. First, the usually overlooked intermediation role of strong local, self-help, and typically non-state institutions in peasant communities that enables marginalised households to assert their interests in interactions with both state and market structures appear as a key factor in mitigating violence and criminal activity. Second, land tenure security, access to public services, and diversifying local economies that draw land and labour away from illicit coca production could address the factors that draw in poor subsistence farmers, including unemployed and under-employed rural workers, to the illicit trade. This paper presents a documentation of the study tour, elaborates on the thinking behind the two explanations, and flags signposts for possible use in improving public policy on drugs and development.1